Pristapni predavana, prilozi i bibliografija na novite çlenovi na Makedonskata Akademija na Naukite i Umetnostite XVI = Opening addresses, contributions and bibliography of the new members of the Macedonian Academy of Sciences and Arts XVI (Skopje)
234 s.